Persistence of Beauveria bassiana (Bals.) Vuill. on the ground over time - LÓPEZ-N., JUAN C.; RIVERA-M., ARMANDO; BUSTILLO-P., ALEX E.; CHAVEZ-C., BERNARDO (Revista Colombiana de Entomología, 1995)
The viability of B. bassiana evaluated through time (3, 8, 41, 95, 148, 218 days) in artificially contaminated soil with 1 mi (108 con/ ml), previously sterilized (SS) or not sterilized (NSS) was investigated under laboratory conditions. The soil was stored in Petri dishes at 25 ± 2°C. In order to evaluate the effect of soil type on the fungus, the Colony Forming Units (CFU) was recovered on SDA and on a selective medium (SM) using the soil dilution píate method. The mean number of viable conidia was calculated and then converted to CFU per g of dried soil. On the SM the fungus was recovered at 148 d (9.5 ± 4.0 x 1W CFU/g) and at 218 d (1.7 ± 1.8 x 103 CFU/g) in NSS. In SS at 148 d, 9.8 ± 2.1 x 103 CFU/g and at 218 d, 9.0 ±6.0 x 102 CFU/g of B. bassiana were recovered. The fungus was not recovered on SDA. During the assay, the mean number of viable conidia declined through time. However, an unexpected temporary in-crease in the number of CFU was observed at 41 d (1.67 x 105 CFU/g in SS on SDA and 8.9 x 105 CFU/g in SS on SM) and at 8 d (7.0 x 104 CFU/g in NSS on SDA and 3.0 x 104 CFU/ g in NSS on SM). The reasons for this increase are yet unknown.